Understanding climate-human interactions in Small Island Developing States (SIDS): Implications for future livelihood sustainability. Issue 2 (25th September 2017) - Nunn, Patrick; Kumar, Roselyn
Abstract : Purpose: Climate change poses diverse, often fundamental, challenges to livelihoods of island peoples. The purpose of this study is to demonstrate that these challenges must be better understood before effective and sustainable adaptation is possible. Design/methodology/approach: Understanding past livelihood impacts from climate change can help design and operationalize future interventions. In addition, globalization has had uneven effects on island countries/jurisdictions, producing situations especially in archipelagoes where there are significant differences between core and peripheral communities. This approach overcomes the problems that have characterized many recent interventions for climate-change adaptation in island contexts which have resulted in uneven and at best only marginal livelihood improvements in preparedness for future climate change. Findings: Island contexts have a range of unique vulnerability and resilience characteristics that help explain recent and proposed responses to climate change. These include the sensitivity of coastal fringes to climate-environmental changes: and in island societies, the comparatively high degrees of social coherence, closeness to nature and spirituality that are uncommon in western contexts. Research limitations/implications: Enhanced understanding of island environmental and social contexts, as well as insights from past climate impacts and peripherality, all contribute to more effective and sustainable future interventions for adaptation. Originality/value: The need for more effective and sustainable adaptation in island contexts is becoming ever more exigent as the pace of twenty-first-century climate change increases.